MODEL PEMBERDAYAAN EKONOMI PEREMPUAN PENENUN DESA SUKARARA BERBASIS MAQASHID SYARIAH - Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy (Yayasan Nusantara Hasana Berdikari, 2024)
Economic empowerment of women micro-entrepreneurs in rural areas plays a crucial role in reducing poverty and improving family welfare. Sukarara Village, Central Lombok Regency, is famously known as a center for traditional songket weaving crafts driven predominantly by women. Despite its vast cultural and economic potential, women weavers still face classic structural challenges, including capital constraints, dependence on middlemen, low financial literacy, and sub-optimal access to digital markets. This Community Service (PkM) activity aims to implement a Sharia Maqashid-Based Economic Empowerment Model to foster blessed and sustainable financial independence. The methodology employed encompasses baseline surveys, problem mapping, sharia business management training, digital marketing mentorship, and facilitating access to interest-free sharia microfinance. Program evaluation indicates an enhanced capacity of partners in financial bookkeeping, market expansion to outer regions through e-commerce, and the realization of a business ecosystem that safeguards spiritual values (hifdz ad-din), life (hifdz an-nafs), intellect (hifdz al-aql), lineage (hifdz an-nasl), and wealth (hifdz al-mal).